Neurodevelopmental disorders and anti-epileptic treatment in a patient with a SATB1 mutation: A case report - Ying Yu; Cuiyun Li; Wei Li; Liting Chen; Dan Wang; Jie Wang; Jian Wang; Jian Wang; Ruen Yao; Ruen Yao (Frontiers Media S.A., 2022)
SATB1 variants causing developmental delay with dysmorphic facies and dental anomalies have been reported in a small cohort. Most patients present epilepsy as a main clinical feature in neurodevelopmental disorders; however, its treatment is unknown. Here, we present a Chinese patient with a de novo truncating variation in SATB1 who presented with mild developmental delay. We disclose the detailed anti-epileptic pharmacological treatment that enabled a favorable outcome. Our study provides important information that may aid clinicians in the prognosis and treatment of rare neurological developmental disorders caused by gene mutations.